Atlantic‐Origin Cold Saline Water Intrusion and Shoaling of the Nutricline in the Pacific Arctic. Issue 6 (25th March 2021) - Jung, Jinyoung; Cho, Kyoung‐Ho; Park, Taewook; Yoshizawa, Eri; Lee, Youngju; Yang, Eun Jin; Gal, Jong‐Ku; Ha, Sun‐Yong; Kim, Soobin; Kang, Sung‐Ho; Grebmeier, Jacqueline M.
Abstract: Atlantic‐origin cold saline water has previously not been considered an important contributor to the nutrient supply in the Pacific Arctic due to the effective insulation by the overlying Pacific‐origin waters that separate the surface mixed layer from the deeper Atlantic Water. Based on hydrographic observations in the northwestern Chukchi Sea from 2015 to 2017, we demonstrate that the intrusion of Atlantic‐origin cold saline water into the halocline boundary between Pacific and Atlantic‐origin waters in 2017 lifted Pacific‐origin nutrients up to the surface layer. We find that the cyclonic atmospheric circulation in 2017 was considerably strengthened, leading to lateral intrusions of two bodies of cold halocline water from the Eurasian marginal seas into the northwestern Chukchi Sea. Our results reveal that the intrusions of cold halocline waters caused unprecedented shoaling of the nutricline and anomalously high surface phytoplankton blooms in typically highly oligotrophic surface waters in the region during summer. Plain Language Summary: Nutrient depletion, especially nitrogen, in Arctic surface waters during the summer is common due to biological uptake and intense stratification caused by sea ice melting and riverine water inputs, which restricts the upward mixing of nutrients into the euphotic zone. Although Atlantic‐origin cold saline water has previously not been considered an important contributor to the nutrient supply in the Pacific Arctic, the results presented here show that the intrusion of Atlantic‐origin cold saline water into the halocline boundary layer between Pacific and Atlantic‐origin waters in the summer of 2017 was an essential mechanism responsible for transporting Pacific‐origin nutrients to the surface layer, leading to anomalously high surface phytoplankton blooms in typically highly oligotrophic surface waters in the northwestern Chukchi Sea. Key Points: The nutricline shoaling by an intrusion of Atlantic‐origin cold saline water was observed in the northwestern Chukchi Sea in 2017 Pacific‐origin nutrients were lifted up to the surface layer by the intrusion of Atlantic‐origin cold saline water The enhanced cyclonic ocean circulation triggered a pronounced transport of Atlantic‐origin cold saline water to the western Arctic Ocean